Effect of different amounts of graphene on metal friction and wear during the mixing process. Issue 10 (8th July 2021) - Han, Deshang; Wang, Kongshuo; Bian, Huiguang; Yan, Gang; Wang, Chuansheng
Abstract: Internal mixer is one the most commonly used rubber‐mixing equipment, which has been applied for decades. This device can operate continuously for a long time. Accordingly, it is quite probable to have wear of the end face of the mixer. Studies show that the end face wear increases the gap between the mixing chamber and the end face, resulting in material leakage, reducing the mixing effect and ultimately affecting the properties of the compound. Therefore, it is of significant importance to study the friction and wear of the mixing compound to the metal in the mixing process. Considering the superior characteristics of graphene (GE), it is considered a revolutionary material and has been widely applied in numerous applications. In the present study, the influence of the mixing compound with different amounts of GE on the friction and wear of the metal end face was analyzed and the ratio of the corrosion wear to abrasive wear was calculated for the first time. It was found that as the amount of GE increases, the proportion of abrasive wear on the metal increases, the proportion of corrosive wear on the metal decreases, and the metal wear decreases first and then increases. Moreover, the lowest metal wear can be achieved when the amount of GE is 3 phr. Abstract : Considering the superior characteristics of graphene (GE), it is considered a revolutionary material and has been widely applied in numerous applications. In the present study, the influence of the mixing compound with different amounts of GE on the friction and wear of the metal end face was analyzed and the ratio of the corrosion wear to abrasive wear was calculated for the first time. It was found that as the amount of GE increases, the proportion of abrasive wear on the metal increases, the proportion of corrosive wear on the metal decreases, and the metal wear decreases first and then increases. Moreover, the lowest metal wear can be achieved when the amount of GE is 3 phr.